Localization of mRNAs coding for peroxisomal proteins in the yeast, Saccharomyces cerevisiae - Zipor, Gadi (National Academy of Sciences, 2009)
Targeted mRNA trafficking and local translation may play a significant role in controlling protein localization. Here we examined for the first time the localization of all (≈50) mRNAs encoding peroxisomal proteins (mPPs) involved in peroxisome biogenesis and function. By using the bacteriophage MS2-CP RNA-binding protein (RBP) fused to multiple copies of GFP, we demonstrated that >40 endogenously expressed mPPs tagged with the MS2 aptamer form fluorescent RNA granules in vivo. The use of different RFP-tagged organellar markers revealed 3 basic patterns of mPP granule localization: to peroxisomes, to the endoplasmic reticulum (ER), and nonperoxisomal. Twelve mPPs (i.e., PEX1, PEX5, PEX8, PEX11–15, DCI1, NPY1, PCS60, and POX1) had a high percentage (52%–80%) of mRNA colocalization with peroxisomes. Thirteen mPPs (i.e., AAT2, PEX6, MDH3, PEX28, etc.) showed a low percentage (30%–42%) of colocalization, and 1 mPP (PEX3) preferentially localized to the ER. The mPPs of the nonperoxisomal pattern (i.e., GPD1, PCD1, PEX7) showed ≪30% colocalization. mPP association with the peroxisome or ER was verified using cell fractionation and RT-PCR analysis. A model mPP, PEX14 mRNA, was found to be in close association with peroxisomes throughout the cell cycle, with its localization depending in part on the 3′-UTR, initiation of translation, and the Puf5 RBP. The different patterns of mPP localization observed suggest that multiple mechanisms involved in mRNA localization and translation may play roles in the importation of protein into peroxisomes.